Early Childhood Social-Emotional Development Through Traditional Games in Learning at Mutiara Integrated Islamic Kindergarten Makassar - Ashar, Ashar Ashar; Mania, Sitti; Malik Ibrahim, Misykat; Syamsudduha, St (Lembaga Sembilan Tiga Community, 2024)
This study aims todescribe the achievement of students' social-emotional development through traditional games in learning at Mutiara Integrated Islamic Kindergarten Makassar. Analyzing the supporting and inhibiting factors of the use of traditional games in learning for the socio-emotional development of students at Mutiara Integrated Islamic Kindergarten Makassar. This type of research is classified as qualitative research with a phenomenological approach. The research design used in this study is related questions, prepositions, reviewing literature, data analysis and report writing. Furthermore, data collection techniques are interviews, observations, documentation, and reference searches. Data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation, and conclusion drawn. The results of the research on the achievement of students' social-emotional development through traditional games in learning obtained a description of the results of self-awareness including showing self-ability, knowing one's own feelings, managing one's own emotions, recognizing other people's emotions, and motivating oneself. A sense of self-responsibility includes knowing their rights, obeying class rules, self-regulation, taking responsibility for their behavior for their own good. Prosocial behavior includes playing with peers, sharing with friends, being cooperative with friends, expressing emotions that are appropriate to existing conditions (happy-sad-enthusiastic, etc.). Supporting and inhibiting factors for the use of traditional games in learning for the socio-emotional development of students, results related to the supporting factors for the use of traditional games include teacher awareness, availability of facilities, recognition of educational values, involvement of the learning community, and family environment. Factors inhibiting the use of traditional games include health conditions, the influence of technology, and diverse interests.